IMPLEMENTASI MEDIA PERMAINAN BINGO SEBAGAI UPAYA UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG SISWA (SLB) - Anastasia Sarabiti Openg; Rinaldi Yusup (STKIP Subang, 2026)
Numeracy skills are a basic part of learning math, but students in Special Needs Schools often find it hard to understand math ideas when they only use traditional teaching methods. This internship report looks at how a bingo game was used as a way to help SLB students improve their numeracy skills. The activities took place in three steps: first, planning; second, carrying out learning activities with bingo; and third, checking how well the learning went. The results show that using bingo as a teaching tool helps students become more interested and involved in their lessons, and it also helps them improve their math skills. So, playing bingo games can be a fun and effective way to learn. This learning tool helps students get involved more, makes them feel more sure about solving math problems, and creates a classroom where people learn together and talk more. The process of carrying out the implementation showed that students started to pay more attention to instructions and showed more excitement during their learning activities. They could more easily spot numbers, do easy math, and use basic math ideas during class activities. The game-based method also made math lessons less boring, allowing students to learn in a more fun and engaging way. Also, teachers could give quick feedback and better understand what each student needs to learn. Overall, the results show that using educational games in math lessons can help create a more inclusive learning environment, increase student involvement, and support the growth of important math skills for students with special needs in different learning situations, while also encouraging teamwork, participation, and self-reliance. Keywords: Bingo, numeracy skills, (SLB) students ung, siswa (SLB)